(untitled) (Sebha University Conference Proceedings, 2024)
Mortar is the bonding agent that integrates brick into a masonry assembly. Mortar must be strong, durable, and capable of keeping the masonry intact, and it must help to create a water-resistant barrier. The qualities, quantities, and content of the components in the mortar affect these needs. The purpose of this study is to compare the compressive strength and engineering qualities of Soukanah (Al-Jufra) limestone (SLS) when it is partially substituted for Portland cement powder in mortar. Limestone substituted in part for cement is regarded as 5, 10, 15, 20, 25, 30, 35, and 40%. Samples of hardened cement mortar are tested for compressive strength after 28 days of age. The greatest compressive strength is only reached at 5% replacement, according to the results. This finding makes it evident that (SLS) can be used as a good 5% replacement for cement in cement mortar mixtures.